Secondary prevention of cervical cancer by screen-and-treat approach among HIV negative women in Faith Alive Hospital, Jos Nigeria - Onyeji, John; Osayi, Emmanuel; Isichei, Mercy W.; Anyaka, Charles U.; Isichei, Christian O.; Sagay, Solomon A.; Christopher, Perpetual C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Cervical cancer is the second most common cancer among women in Nigeria and the leading cause of cancer-related death in sub-Saharan Africa. In low-income settings, visual inspections with acetic acid (VIA) and Lugol’s iodine (VILI); and subsequent treatment of cervical precancerous lesions with thermal ablation remains the practical approach for secondary prevention. Objectives were to determine prevalence of pre-cancerous cervical lesions, prevalence of suspected cervical cancer, and associated risk factors. Methods: A retrospective study on sexually active HIV negative women aged 16-55 years screened for cervical cancer using VIA/VILI within 16 months period in Faith Alive Hospital Jos. Data were analyzed using IBM-SPSS 26. Socio-demographic characteristics and screening results were presented in frequency tables; and logistic regression was performed to determine risk factors for cervical pre-cancerous lesions. Results: 1,073 HIV negative women were screened for cervical cancer using VIA/VILI. 82 (7.6%) tested positive, 30 (2.8%) had suspected cancer with modal age distribution of 36-45 years. Higher positivity yield (58.6%) was found in ages between 36 and ≥55 years while the less positivity yield (41.4%) was found ages ≤35 years. Parity ≥3 had 1.8 fold risk association with precancerous lesion. Conclusions: Our study revealed high prevalence of cervical pre-cancerous lesions among HIV negative women, modal age distribution for suspected cancer and parity ≥3 being significant risk factor. Thus, “screen-and-treat” approach to cervical cancer prevention by VIA/VILI and thermal ablation in resource constraint settings should be undertaken until widespread HPV testing to triage clients is possible.